2013
DOI: 10.1371/journal.pone.0073612
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization Mediates Thermo-Adaptation, Substrate Affinity and Transglycosylation in a Highly Thermostable Maltogenic Amylase of Geobacillus thermoleovorans

Abstract: BackgroundMaltogenic amylases belong to a subclass of cyclodextrin-hydrolyzing enzymes and hydrolyze cyclodextrins more efficiently than starch unlike typical α-amylases. Several bacterial malto-genic amylases with temperature optima of 40–60°C have been previously characterized. The thermo-adaption, substrate preferences and transglycosylation aspects of extremely thermostable bacterial maltogenic amylases have not yet been reported.Methodology/Principal FindingsThe recombinant monomeric and dimeric forms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 31 publications
3
19
0
Order By: Relevance
“…In this study, command lines of MODELLER program were used for construction of a 3D dimeric form of CDase. Structural examination of the modelled enzyme confirmed that the central domain in the CDase has the functional property as described by Fritzsche et al and Unban et al Structural features of the enzyme show that the position of active sites in the dimeric form of the enzyme allows small‐sized substrates better entrance to the reaction site …”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…In this study, command lines of MODELLER program were used for construction of a 3D dimeric form of CDase. Structural examination of the modelled enzyme confirmed that the central domain in the CDase has the functional property as described by Fritzsche et al and Unban et al Structural features of the enzyme show that the position of active sites in the dimeric form of the enzyme allows small‐sized substrates better entrance to the reaction site …”
Section: Discussionsupporting
confidence: 62%
“…The ratio of k cat / K m as an indication of substrate specificity for different substrates increases as α‐CD>β‐CD>γ‐CD. The resulting data of this study show that the recombinant CDase had more specificity toward α‐CD . Similar to CDase‐ZNU, α‐CD is the specific substrate for the CDase isolated from A. flavithermus (AAX29991.1) .…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…G3Amy inefficiently hydrolyzed cyclodextrins (Table 2) as compared to that of other exo-α-amylases such as Geobacillus maltogenic amylases (Mehta and Satyanarayana 2013;Nasrollahi et al 2013). This indicated that the nonreducing end of a substrate was helpful to recognize the substrate, but not essential for hydrolysis by G3Amy unlike β-amylases.…”
Section: Discussionmentioning
confidence: 96%